Legal regulation of the promise to sell real estate in the light of Saudi and comparative regulations - Wasifa Fawaz Zaki (International Journal of Law Research and Studies, 2025)
The promise to sell real estate is considered a preliminary agreement in which one or both parties commit to concluding a future contract of sale upon the fulfillment of certain conditions. This legal act is characterized by the fact that it does not immediately transfer ownership; rather, it creates an obligation to enter into a binding sale contract at a later time, thus classifying it as a preparatory contract. This study is divided into three sections: The first section discusses the fundamental elements of the promise to sell real estate; The second examines how it differs from other legal dispositions; The third explores the various forms of real estate sale promises. The study reached several key findings, the most important of which is that the promise to sell constitutes a valid contract, which may be binding on one or both parties, and it may take the form of a reciprocal promise. Its legal effects vary depending on its nature. The study concluded with several recommendations, the most prominent being the necessity of explicitly addressing the promise to sell real estate in legal texts and regulating its provisions due to its practical and social significance.
Keywords: Promise to Sell; Preliminary Contracts; Real Estate Sale; Contractual Obligation